Encoding of Variant Taxonomies in TEI - Helena Bermúdez Sabel (OpenEdition, 2019)
The inherent flexibility of the digital format has favored the rise of editions that enable access to every witness of a particular textual work. These types of editions might have different goals and seek to answer different research questions, but they usually coincide in drawing attention to the importance of textual variants. To maximize the computational analysis that may be practiced with the variants in different witnesses, a complex taxonomy that reflects the diversity of cases is required. Many scholars have followed the recommended TEI method for encoding types of variants—that is, through the attributes @cause or @type inside the element <rdg>—while others find that method insufficient. These attributes are not able to enclose the hierarchy intrinsic to complicated taxonomies or the overlap of classes in an efficient way. However, the TEI Guidelines do offer a module that addresses this complex encoding issue: feature structures. The method proposed in this paper does not advocate for a controlled vocabulary to categorize types of variants. What it offers instead is a pliable encoding method that allows the editor to include multiple layers of information in each apparatus tagset.